2003
DOI: 10.1038/nature01850
|View full text |Cite
|
Sign up to set email alerts
|

Integration of interferon-α/β signalling to p53 responses in tumour suppression and antiviral defence

Abstract: Swift elimination of undesirable cells is an important feature in tumour suppression and immunity. The tumour suppressor p53 and interferon-a and -b (IFN-a/b) are essential for the induction of apoptosis in cancerous cells and in antiviral immune responses, respectively, but little is known about their interrelationship. Here we show that transcription of the p53 gene is induced by IFN-a/b, accompanied by an increase in p53 protein level. IFN-a/b signalling itself does not activate p53; rather, it contributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

36
710
12
18

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 823 publications
(776 citation statements)
references
References 44 publications
36
710
12
18
Order By: Relevance
“…A recent report showed that transcription of the p53 gene is induced by IFN-a, accompanied by an increase in p53 protein level (Takaoka et al, 2003). The study suggested that p53 gene might be an important predictor of IFN-a therapy for HCV liver cirrhosis and HCC.…”
Section: Discussionmentioning
confidence: 92%
“…A recent report showed that transcription of the p53 gene is induced by IFN-a, accompanied by an increase in p53 protein level (Takaoka et al, 2003). The study suggested that p53 gene might be an important predictor of IFN-a therapy for HCV liver cirrhosis and HCC.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, the IFN-stimulated gene factor3 (ISGF3) formed by IFN-a has been shown to induce p53 gene expression by binding to at least two IFN-stimulated response element (ISRE) sites in the p53 gene (Takaoka et al, 2003;Vilcek, 2003). We found that while the HepG2 tumours of PEG-IFN-and combination-treated animals showed significantly elevated p53 protein and mRNA levels, only the combination-treated tumours showed increased p53 phosphorylation at serine46 and elevated p53AIP1 mRNA levels.…”
Section: Discussionmentioning
confidence: 87%
“…Given the central role p53 plays in the induction of cell cycle arrest and apoptosis, it is possible that the IFN-a/5-FU combination therapy activates p53 in some way. Supporting this is that IFN-a has been found to induce p53 gene expression (Takaoka et al, 2003;Vilcek, 2003). To test whether p53 participates in the anti-HCC activity of IFN-a/5-FU combination therapy, we here treated nude mice carrying HepG2 cell tumours with 5-FU and/or IFN-a.…”
mentioning
confidence: 96%
See 2 more Smart Citations